Digital Technologies for Emotion-Regulation Assessment and Intervention: A Conceptual Review. (January 2022) - Bettis, Alexandra H.; Burke, Taylor A.; Nesi, Jacqueline; Liu, Richard T.
The ability to regulate emotions in response to stress is central to healthy development. Whereas early research in emotion regulation predominantly employed static, self-report measurement, the past decade has seen a shift in focus toward understanding the dynamic nature of regulation processes. This is reflected in recent refinements in the definition of emotion regulation that emphasize the importance of the ability to flexibly adapt regulation efforts across contexts. The latest proliferation of digital technologies employed in mental health research offers the opportunity to capture the state- and context-sensitive nature of emotion regulation. In this conceptual review, we examine the use of digital technologies (ecological momentary assessment; wearable and smartphone technology, physical activity, acoustic data, visual data, and geo-location; smart-home technology; virtual reality; social media) in the assessment of emotion regulation and describe their application to interventions. We also discuss challenges and ethical considerations and outline areas for future research.